Communication as Mediator: Interprofessional Deprescribing and the RCC (Roles–Collaboration–Communication) Framework - Alina Cernasev; Devin Scott; Laura Reed; Amy Hall; Bruce L. Keisling (Healthcare, 2026)
Background: Polypharmacy remains a significant challenge, often leading to adverse drug events and increased healthcare costs. One effective strategy to mitigate these risks is deprescribing, the systematic and intentional discontinuation or reduction of medications. Despite growing recognition of deprescribing’s importance, limited research has examined the impact of interprofessional education interventions on developing deprescribing competencies among healthcare professional students. This study aims to examine the perspectives of healthcare students, including student pharmacists, medical students, and nurse practitioner students, regarding their roles and responsibilities in the deprescribing process. Methods: Following completion of a Deprescribing Interprofessional Education Simulation activity (DIPE-SA), participants were invited to join focus groups. The study included students from the University of Tennessee Health Science Center (UTHSC) Colleges of Medicine, Nursing, and Pharmacy. Constructivist Grounded Theory (CGT) underpinned the qualitative research approach, informing the development of the study framework. Each focus group was facilitated by two researchers and recorded. Recruitment continued until saturation was achieved. Data were transcribed verbatim and analyzed for themes using Dedoose, qualitative analysis software. Results: A total of 19 participants attended four focus groups. Three major themes emerged and guided the development of the Roles–Collaboration–Communication (RCC) interprofessional framework. The first theme, roles, focuses on the unique responsibilities and functions healthcare professionals assume within the team and throughout the deprescribing process. The second theme, collaboration, emphasizes coordinated efforts and shared decision-making among members of the interprofessional healthcare team in deprescribing. Finally, the third theme, communication, highlights the importance of effective information and intention exchange, serving as both a mediator and connector, linking roles and collaboration, and ultimately enabling successful deprescribing. Conclusions: This study’s findings, together with the RCC interprofessional framework, demonstrate the interplay of roles, collaboration, and communication in medication management. The RCC framework highlights the value of dynamic team processes for achieving safe and effective deprescribing, which in turn improves patient care and health outcomes.